Women artists: recognition and reappraisal from the early Middle Ages to the twentieth century - Petersen, Karen; Wilson, J. J. (Harper colophon books ; CN 387, 1976)
Commentary on and photographs of sculpted and painted images of women created by women shed light upon feminine self-perceptions and the contributions of women artists through the centuries
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques